Formula Student car chassis – research on the torsional stiffness - Wolska Natalia; Szyca Mikołaj; Estrada Quirino; Castaneda Leonel (MATEC Web of Conferences, 2024)
In the article, the torsional stiffness of a formula student's space frame was analyzed. The article mainly focuses on the comparison of the stiffness between different frame designs, which were used in three consecutive formula student cars designed by the weracing™ team as well as a comparison of the result of two calculation methods. The calculations were made in computer-aided engineering software, i.e. ABAQUS dedicated to analyzing Finite Elements models. The assumption for analysis was to check the rotation of the frame after applying a 5000 Nm load. The torsional load was introduced by first fixed the four rear bulkhead joint and then subsequently applying a force couple to the upper front wishbone mounts. Having a distance between joint from the central line and torque moment, the force for specific nodes can be calculated. The calculation for each model was performed. The obtained differences result from the construction of frames and applied methods of calculations.